Troubling recognitions in British responses to modern slavery - Gadd, David (The British journal of criminology, 2018)
This article interrogates the advent of modern slavery policy in Britain, explaining how the police and NGO sector have welcomed an organized crime model, politically conceived in ‘excessively positive’ terms. Deploying Christopher Bollas’ (1993: 167) concept of ‘violent innocence’, defined as a defence against the ‘desire to be innocent of a troubling recognition’, we argue that the politics of modern slavery render it difficult for many to imagine offenders as anything other than the ‘evil’ nemesis of ‘innocent’ victims. The article argues for the need to be mindful of Britain’s historical role in the advent of slavery and practices like it, and recognition of the extent to which immigration control practices exacerbate the vulnerabilities to exploitation modern slavery policy attempts to tackle.